2007
DOI: 10.1017/s136898000720494x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological survey of vitamin deficiencies in older Thai adults: implications for national policy planning

Abstract: Objective: To examine the prevalence and risk factors of vitamin deficiencies among older Thai adults. Methods: The cross-sectional study was conducted in four rural communities, one from each of the four main regions of Thailand. In total, 2336 subjects aged 60 years and over were recruited. Anthropometric variables, demographic data, blood glucose and lipid profile, albumin, globulin and blood levels of vitamin A, b-carotene, folic acid, vitamin B 12 , vitamin C, vitamin E and vitamin B 1 were all measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Another physiological-pathological condition that may match such a severe folate deprivation state is nutritional folate deficiency or insufficiency. Indeed folate deficiency affects ϳ10% of the population as well as more than 50% of the children and elderly that live in poverty in the United States, Thailand, and rural areas of India (38,57,58). Hence under such physiological-pathological conditions of severe folate deficiency, RFC and GGH may possibly undergo a significant down-regulation in gene expression and activity to protect cells from further loss of intracellular folates due to folate efflux via the RFC.…”
Section: Resultsmentioning
confidence: 99%
“…Another physiological-pathological condition that may match such a severe folate deprivation state is nutritional folate deficiency or insufficiency. Indeed folate deficiency affects ϳ10% of the population as well as more than 50% of the children and elderly that live in poverty in the United States, Thailand, and rural areas of India (38,57,58). Hence under such physiological-pathological conditions of severe folate deficiency, RFC and GGH may possibly undergo a significant down-regulation in gene expression and activity to protect cells from further loss of intracellular folates due to folate efflux via the RFC.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to vitamin B 12 deficiency, it is unlikely that this problem would occur within the Thai population, as daily diets routinely include the ingestion of fish sauce, a rich source of vitamin B 12 [25]. Several previously conducted studies also lend support to the contention that vitamin B 12 and folate deficiencies remain relatively rare in the Thai population [26,27,28]. …”
Section: Discussionmentioning
confidence: 99%
“…Other nutritional deficiencies of importance for being anemic include vitamin A, vitamin B12, and folate. However, these micronutrient deficiencies are relatively low in Thailand [1,2,16,25,26]. Among the non-nutritional factors, malaria and hookworm infestation also might contribute to the occurrence of anemia [4,5,17], but based on the cumulative data from community hospitals located in the study area, these two diseases were quite seldom found among the patients of the hospitals and the children under survey.…”
Section: Discussionmentioning
confidence: 99%